Frost nucleation and growth on hydrophilic, hydrophobic, and biphilic surfaces - Van Dyke, Alexander Scott (Kansas State University, 2015)
The purpose of this research was to test if biphilic surfaces mitigate frost and ice formation. Frost, which forms when humid air comes into contact with a surface that is below the dew point and freezing temperature of water, hinders engineering systems such as aeronautics, refrigeration systems, and wind turbines. Most previous research has investigated increasingly superhydrophobic materials to delay frost formation; however, these materials are dependent on fluctuating operating conditions and surface roughness. Therefore, the hypothesis for this research was that a biphilic surface would slow the frost formation process and create a less dense frost layer, and water vapor would preferentially condense on hydrophilic areas, thus controlling where nucleation initially occurs. Preferential nucleation can control the size, shape, and location of frost nucleation. To fabricate biphilic surfaces, a hydrophobic material was coated on a silicon wafer, and a pattern of hydrophobic material was removed using photolithography to reveal hydrophilic silicon-oxide. Circles were patterned at various pitches and diameters. The heat sink was comprised of two parts: a solid bottom half and a finned upper half. Half of the heat sink was placed inside a polyethylene base for insulation. Tests were conducted in quiescent air at room temperature, 22 °C, and two relative humidities, 30% and 60%. Substrate temperatures were held constant throughout all tests. All tests showed a trend that biphilic surfaces suppress freezing temperature more effectively than plain hydrophilic or hydrophobic surfaces; however, no difference between pattern orientation or size was noticed for maximum freezing temperature. However, the biphilic patterns did affect other aspects such as time to freezing and volume of water on the surface. These effects are from the patterns altering the nucleation and coalescence behavior of condensation.
Keywords: Frost formation; Biphilic; Nucleation; Phase change heat transfer; Surface enhancement; Mechanical Engineering (0548)